Development of a high strength, low density and corrosion resistant novel FeCrMoNb1.5Ti0.5 complex concentrated alloy - Yadav D.K.; Shadangi Y.; Yadav S.D.; Sinha S. (My University, 2025)
The present work deals with the microstructure, mechanical properties and corrosion behavior of a FeCrMoNb1.5Ti0.5 complex concentrated alloy (CCA). The aforementioned alloy was fabricated by vacuum arc melting technique. The observed density and lattice parameters of the as-cast alloy are 7.821 g/cm3 and 3.179 ± 0.003 Å, respectively, which follow the rule of mixture. The phase evolution, chemical composition, and microstructure in the as-cast condition, as well as after annealing treatment at 800°C, 1000°C, and 1200°C, were investigated through XRD, TEM, and SEM-EDS. The XRD and TEM analyses confirmed the presence of BCC structure with minor amount of TiCr2 type and NbCr2 type C14 Laves phases. Instrumented micro-indentation and corrosion testing were performed in the as-cast and annealed specimens. The microhardness of the as-cast alloy was 825 HV and it increased to 1102 HV after annealing at 1200ºC for 20 h. This peak hardness was achieved after annealing at 1200ºC due to the presence of a large volume fraction of Laves phase. Potentiodynamic polarization tests of the as-cast and as-annealed specimens revealed outstanding corrosion resistance of the CCA compared to stainless steel. This is attributed to better microstructural homogeneity and reduced elemental segregation after annealing. © 2023 Elsevier Ltd